Subarachnoid Hemorrhage Associated with Ventricular Fibrillation and Out-of-Hospital Cardiac Arrest - Hidetada Fukushima; Kenji Nishio; Kazuo Okuchi (Case Reports in Medicine)
Aneurysmal subarachonoid hemorrhage (SAH) is a common cause of out-of-hospital cardiac arrest (OHCA). Even after successful resuscitation, most of these SAH patients suffer brain death or enter a vegetative state. To our knowledge, survival without neurological damage from SAH following OHCA is quite a rare event. We treated a case of SAH who presented with OHCA and survived without neurological sequelae. A 50-year-old woman presented with ventricular fibrillation (VF), and was successfully resuscitated before hospital arrival. Since there was no evidence of acute coronary syndrome, a head CT scan was performed and established the diagnosis of SAH. On arrival, she was comatose, however, 3 hours after admission, her neurological status recovered. She underwent treatment for the ruptured aneurysms and was discharged from hospital without any neurological deficits.